2014
DOI: 10.1007/s12671-014-0359-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-Compassion and Well-Being in Parents of Children with Autism

Abstract: Parents of children with autism are faced with difficult and unique daily stressors associated with their child's disorder. The personal characteristics of parents can influence how they approach stressful life events and potentially help them cope with some of the deleterious effects associated with extreme stress. One factor that may be an important coping strategy is self-compassion, which involves being kind to oneself in times of difficulty, recognizing the shared nature of human suffering, and being mind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
139
1
23

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(206 citation statements)
references
References 75 publications
10
139
1
23
Order By: Relevance
“…In addition, our findings work in concert with previous studies that indicated the beneficial effects of mindfulness on well-being across special populations, such as body dissatisfaction in women (Albertson, Neff, & Dill-Shackleford, 2015) and parents of children with autism (Neff & Faso, 2015).…”
Section: The Moderating Role Of Mindfulness On Gratitudesupporting
confidence: 86%
“…In addition, our findings work in concert with previous studies that indicated the beneficial effects of mindfulness on well-being across special populations, such as body dissatisfaction in women (Albertson, Neff, & Dill-Shackleford, 2015) and parents of children with autism (Neff & Faso, 2015).…”
Section: The Moderating Role Of Mindfulness On Gratitudesupporting
confidence: 86%
“…In other words, the discrepancy between the level of compassion given to oneself versus to others appears to be larger among women than men (Neff & Pommier, 2013). This is unfortunate because research indicates that self-compassion helps prevent the stress and burnout often experienced by caregivers (Barnard & Curry, 2012;Neff & Faso, 2014;Shapiro, Brown, & Biegel, 2007). It may be particularly helpful for women to receive direct training in self-compassion, therefore, in order to learn how to balance caring for themselves and others.…”
Section: Discussionmentioning
confidence: 99%
“…() found that higher levels of self‐compassion were associated with decreased parenting stress. Similarly, Neff and Faso () found that self‐compassion predicted positive adjustment, including less parental stress, of parents of children with autism.…”
Section: Introductionmentioning
confidence: 89%